Kajian Komprehensif Tafsir bi Isyari dalam Kaidah Penafsiran Ayat Ahkam: Perspektif Kepastian Hukum Islam - Abriman, Rajendra; Athoillah (Adagium: Jurnal Ilmiah Hukum, 2026)
Tafsir bi Isyari is a method of interpreting the Qur'an that emphasizes the inner meaning (batin) and hidden meaning, which differs from the outer meaning (zahir) that is textual. This method is grounded in Hadith (Prophetic tradition) which states that the Qur'an possesses both an outer and inner meaning, and is revealed based on special guidance and inspiration for its experts. This paper comprehensively examines the definition of Tafsir Isyari, the different views of scholars regarding the legality and conditions for accepting Tafsir Isyari, as well as its strengths and weaknesses. The research also presents concrete examples of Qur'anic verses that command in an isyari (allusive/allusional) manner as a form of application of this method. The results of the study indicate that Tafsir Isyari can provide a deep and spiritual understanding, but it must be kept within the principles of Tafsir (exegesis) so that it does not lead to subjectivity and deviation. Therefore, this interpretation holds an important position in the treasury of Tafsir, provided that it is carried out in accordance with scholarly and Sharia principles.